Analisis Gaya kepemimpinan Perempuan di Lembaga Legislatif dalam Perspektif Ketahanan Politik di Daerah (Studi Kasus: Kepemimpinan Rospita Sitorus sebagai wakil ketua DPRD Kabupaten Simalungun) - Sianipar, Tio Masa Elnitin; Hanita, Margaretha (Jurnal Kajian Stratejik Ketahanan Nasional, 2019)
Women's leadership became public issues are always discussed, and has provoked polemics and debate between the pros and cons of women leaders in the country. The issue of women's leadership also always interesting to demand, even today more and more scientists or researchers focused more on the assessment of women's leadership in particular. As in this study examine further how permpuan instituted legislative leadership style. The purpose of this study was to identify and analyze the role of leadership and political participation Rospita Sitorus at the legislative, as well as to analyze the leadership of women in Parliament Simalungun before her.The results of this study found that the lack of involvement of women both in the political infrastructure as well as in the political superstructure. And this, influential in gender policy and still attached to the patriarchal culture in Simalungun. Then, Rospita Sitorus is a transformsional leadership.These results indicate the need to increase women's leadership in the legislature, with the hope to provide a positive influence in the decision making for the community especially those of women's interests.